Human Dignity: A Primordial Theme In The Poetic Works Of Allama Muhammad Iqbal - Dr. Muhammad Iqbal Shahid , Dr. Naseem Ur Rehman , Dr. Almas Khanum , Dr. Saima Iram , Dr. Javed Iqbal , Kiran Aslam , Dr. Babar Nasim Asi , Dr. Ghulam Akber (Migration Letters, 2024)
Allama Muhammad Iqbal is a great poet-philosopher of recent history who gave the idea of Pakistan. He is one of the poets of the world who have a complete ideology in their poetry. Iqbal considers Maulana Rumi as his mentor and “Peer”. Iqbal in his poetry dignifies man as the most important c[1]reature of the universe. He urges the man to improve his Self (Khudi) in order to meet the universal needs of a complete human being and for this improvement, he suggests different stages of training of the Self. He strongly condemns slavery and the nations who exploit other nations’ rights. In this article, Iqbal’s ideology of the human dignity is briefly reviewed.